FYR Macedonia : Country Economic Memorandum Tackling Unemployment - World Bank (Washington, DC, 2013)
Reducing the high rates of unemployment from which the Macedonian economy suffers is a leading priority of the Government. The large share of working age population who are inactive or occupying themselves with low productivity, occasional work represents output foregone and income lost. Moreover, the important goal of sharing the benefits of growth more equitably between groups and regions proves increasingly elusive when many citizens are trapped in long-term unemployment, a state closely linked to household poverty. It seems that the formal job market in the former Yugoslav Republic of Macedonia (FYR Macedonia) has failed. What actions can and should the Government take t o get more people into work? As the authorities strive to solidify peace and stability, accelerate remaining structural reforms, and move policies and institutions towards European norms, the problem of high unemployment cannot be ignored. Very high levels of unemployment discourage the authorities from imposing further s hocks on the economy and may add to the delay of needed structural reforms. But reform of labor market institutions and policies is only one part of the solution, and not the most important. The Government has limited ability to raise labor demand directly. Overall growth and job creation by the private sector will be the only long-term solution. The first chapter of this report sets out a preliminary strategy for long-term growth. It argues that high unemployment is primarily an inheritance from the pre-transition era. Growth has been limited since independence by low investment levels, and to remove this constraint, the Government should be focused on ways t o improve education, create a supportive investment climate (especially for foreign investment and small and medium enterprises), and accelerate free trade as part o f integration into European markets.